ChemInform Abstract: Conjugated Microporous Polymers: Design, Synthesis and Application. Issue 50 (10th December 2013) - Xu, Yanhong; Jin, Shangbin; Xu, Hong; Nagai, Atsushi; Jiang, Donglin
Abstract Review: [114 refs.]